Current progress in CRISPR‐based diagnostic platforms. Issue 3 (26th October 2018) - Khambhati, Khushal; Bhattacharjee, Gargi; Singh, Vijai
Abstract: The CRISPR‐Cas system is a key technology for genome editing and regulation in a wide range of organisms and cell types. Recently, CRISPR‐Cas–based diagnostic platform has shown idealistic properties for pathogen detection. Integrating the CRISPR‐Cas platform along with lateral flow system allows rapid, sensitive, specific, cheap, and reliable diagnostic. It has the potential to be in frontline for not only pathogen detection during the epidemic outbreak, but also cancer, and genetic diseases. Abstract : A recent breakthrough in the field of diagnostic using the CRISPR system has been developed. It is known as SHERLOCK that could detect at an attomolar concentration of nucleic acids. RPA, recombinase polymerase amplification; RT‐RPA, reverse transcriptase‐recombinase polymerase